Joint IODP/ICDP Scientific Drilling of the Chicxulub Impact Crater - Penny Barton (Scientific Drilling, 2007)
The Chicxulub impact crater in Mexico (Fig. 1) is unique in the terrestrial impact record. Its association with the Cretaceous–Paleocene (K-P) mass extinction has generated great interest, but the precise environmental effects and associated extinction mechanisms remain a matter of some debate over several decades. Chicxulub is also the best preserved large impact crater on Earth and is the only known terrestrial impact structure with a demonstrable topographicpeak ring (Figs. 2 and 3). Peak rings are common features of large craters on the terrestrial planets yet their process of formation is poorly understood. At all other large terrestrial craters, erosion and/or tectonic deformation have removed the evidence of a peak ring, should one have existed. Chicxulub is, thus, the only crater where the peak ring can be imaged and sampled.